Phytochemical and Pharmacological Study of Valepotriates in Valeriana officinalis L. F.Valerianeceae Cultivated in Iraq. - Zeina Z. Nagara; Kawkab Y. Saour (College of Pharmacy University of Baghdad, 2017)
This study concerned with phytochemical investigation and methods of extraction and separation of active constituents from Valeriana officinalis plant cultivated in Iraq. Due to the large number of active constituents in Valeriana officinalis, it was necessary to make analytical study of its constituents to determine the chemical nature of these constituents and then determine the main classes (terpenes and iridoids) using chemical reagents specific for each class. Different organic solvents like ethanol (70%) used in soxhlet apparatus and hexane, ethyl acetate and methanol were used separately to extract the main active constituents by maceration. Through comparison between these solvents using thin layer chromatography (TLC), it has been found that hexane was best suited to extract most of the active constituents from the plant by maceration method. Analytical study showed that terpens was separated and purified using preparative TLC and preparative HPLC. Identification of isolated component (valtrate) from roots of plant was obtained using HPLC and PHPLC also depending on some material-specific constants such as infrared spectroscopy (FTIR). Results of analysis showed that Valeriana officinalis cultivated in Iraq is a good source of many constituents with different important pharmacological activities. The pharmacological study showed that the total organic plant extract has sleep induction effect when injected I.P. to experimental mice.  Key wards:  Valeriana officinalis, Valepotriate, Insomnia.